2013
DOI: 10.1007/s00259-013-2564-y
|View full text |Cite
|
Sign up to set email alerts
|

[18F]Flutemetamol amyloid-beta PET imaging compared with [11C]PIB across the spectrum of Alzheimer’s disease

Abstract: [(18)F]FMM PET imaging detects Aβ deposition in patients along the continuum from normal cognitive status to dementia of AD and discriminates AD patients from HC subjects, similar to [(11)C]PIB PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 22 publications
8
81
7
Order By: Relevance
“…The cortical retention of 18 F-flutemetamol has been compared to 11 C-Pittsburgh compound B ( 11 C-PIB) [9] in clinical populations such as amnestic mild cognitive impairment (aMCI) patients together with clinically probable AD patients [10], or aMCI and clinically probable AD together with healthy controls [11], but not in cohorts consisting exclusively of cognitively intact older adults. This is crucial since the discriminative value of a tracer may also depend on the population under study.…”
Section: F-labeled Tracers Currently Approved By the Food And Drugs Amentioning
confidence: 99%
See 2 more Smart Citations
“…The cortical retention of 18 F-flutemetamol has been compared to 11 C-Pittsburgh compound B ( 11 C-PIB) [9] in clinical populations such as amnestic mild cognitive impairment (aMCI) patients together with clinically probable AD patients [10], or aMCI and clinically probable AD together with healthy controls [11], but not in cohorts consisting exclusively of cognitively intact older adults. This is crucial since the discriminative value of a tracer may also depend on the population under study.…”
Section: F-labeled Tracers Currently Approved By the Food And Drugs Amentioning
confidence: 99%
“…The concordance between two tracers may be better in a mixed sample of patients and controls then in a group consisting exclusively of cognitively normal controls. In cognitively intact older adults ligand retention values may lie closer to threshold than in patients with probable AD and it has been hypothesized that 11 C-PIB could potentially outperform 18 Flabelled tracers under such conditions [12]. Other 18 F-labelled amyloid tracers ( 18 F-florbetaben [7], 18 F-florbetapir [8], 18 F-AZD4694 [13]) have also been compared with 11 C-PIB within subjects, again mostly in clinical patient populations combined with cognitively intact older adults [14,15].…”
Section: F-labeled Tracers Currently Approved By the Food And Drugs Amentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggests a larger normal variation in the cerebellar cortical region of interest, and the results of this study would therefore point to the pons as the favored reference region. However, both structures were previously used as reference regions in studies of quantitative accuracy (26,30,31) with good results, suggesting that the graphical definition of the region has an impact. This study found only an insignificantly higher accuracy referencing pons, and even larger and prospective studies would be needed to determine a preference for either structure.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 36 patients with AD, 68 patients with MCI, and 62 controls (stratified by age) demonstrated a strong correlation between the 2 compounds (p < 0.001), along with the ability to discriminate patients with clinically diagnosed AD from older healthy controls with a sensitivity and specificity of 97.2 % and 85.3 %, respectively [34]. However, another study demonstrated that there is increased concordance between both biomarkers, depending on the region of interest (ROI) for comparison.…”
Section: [ 18 F]3'-f-pib or Flutemetamolmentioning
confidence: 99%